2018
DOI: 10.1589/jpts.30.555
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of using exergames as a rehabilitation tool: the attitudes, awareness, opinions and experiences of physiotherapists, and older people towards exergames

Abstract: [Purpose] The aim of this study was to investigate the feasibility of using exergames as a rehabilitation tool by determining the attitudes, awareness, opinions and experiences of physiotherapists, and older people towards exergames. [Subjects and Methods] A cross-sectional study was conducted and two short self-developed questionnaires (for physiotherapists and older people) were distributed in three hospitals in Cork (Ireland) to assess the attitudes towards and familiarity with exergames among physiotherapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Although significantly higher post-intervention flow state scores were found in the standard exercise group, there was no evidence to show absence of flow experience in exergaming. In exergaming programmes run by certain healthcare or rehabilitation centres, clients are supported by their physiotherapist in terms of setting suitable exergaming levels for them, monitoring and prescribing rehabilitative movements for them [ 132 , 133 ]. With this, another consideration is the potential advantage that after initial instruction, exergaming may require less supervision by physiotherapy staff and rely on continuous direct feedback to each patient.…”
Section: Discussionmentioning
confidence: 99%
“…Although significantly higher post-intervention flow state scores were found in the standard exercise group, there was no evidence to show absence of flow experience in exergaming. In exergaming programmes run by certain healthcare or rehabilitation centres, clients are supported by their physiotherapist in terms of setting suitable exergaming levels for them, monitoring and prescribing rehabilitative movements for them [ 132 , 133 ]. With this, another consideration is the potential advantage that after initial instruction, exergaming may require less supervision by physiotherapy staff and rely on continuous direct feedback to each patient.…”
Section: Discussionmentioning
confidence: 99%
“…However, a survey conducted in physiotherapists and elderly subjects showed that the former are aware of the functions and possible applications of exergames, but they do not think that they will have a relevant influence on traditional rehabilitation tools. Conversely, older people have no interest or even information on their function but could be willing to try them for rehabilitation purposes (15).…”
Section: Discussionmentioning
confidence: 99%
“…The impact of serious games on physical therapy has been studied in terms of effectiveness [ 4 - 6 ] and motivational determinants [ 7 , 8 ]. However, as a virtual guide replacing or complementing a real physician, exergaming systems tend to lack objective, clinically meaningful evaluation of patient performance.…”
Section: Introductionmentioning
confidence: 99%